Diferensiasi dalam Perkuliahan Penulisan Kreatif Strategi Meningkatkan Capaian Pembelajaran Berbasis Ekonomi Kreatif dan Teknologi - Moh. Arif Susanto; Adi Setiawan; Furoidatul Husniah; Arisni Kholifatu Amalia Shofiani; Rizky Abrian (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe a differentiated learning approach in creative poetry writing lectures as a strategy to improve learning achievement based on the creative economy and technology. Using quantitative descriptive methods, with percentage data analysis. The subjects of the study were 40 students of the 2022 intake who were programmers of the Creative Writing course. The research data were in the form of initial formative assessment results at the beginning of the lecture and final summative assessment at the end of the lecture which had the same assessment focus on knowledge and skills with the same instrument. Formative assessments in learning, RPS, and RPP were used as secondary data. Data collection techniques with objective tests on initial formative assessments of learning and non-objective on final summative assessments of learning. The results of the study, in the initial formative assessment of learning focused on knowledge and skills showed scores with a low category of 5%, medium 60%, and high 35% increased in the final summative assessment of learning with a low score category of 0%, medium 15%, and high 85%. The differentiated learning method when applied in the integration of the MBKM and OBE curriculum, offers a holistic and adaptive approach to learning. Differentiated learning by adjusting the process to individual learning achievements, needs, interests, and learning styles, not only improves learning achievements in writing poetry but also improves technology usage skills and is able to produce derivative poetry products that have economic value.